Katuwana. A Dutch Fort in Southern Sri Lanka - Garusinha, S. Sampath; Boekel, Rudolf J.; Weisshaar, Hans-Joachim (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Katuwana was one of the small fortresses that the Dutch Verenigde Oostindishe Compagnie built in the second half of the 17th century to ensure its boundaries against the territory of the Kandyan kingdom and to promote the Compagnie’s spice trade. The garrison of about 40 soldiers had to prevent raids from the central hills into the low lands of the coastal belt. Excavations were carried out prior to conservation work. Archaeological research was especially interesting as the contemporary witness J. W. Heydt gave a detailed description with a plan and an engraving of the front view of the fortress during its main period in the fi rst half of the 18th century. Most of the exposed rooms around the inner courtyard could be identifi ed due to Heydt’s remarks. The article will be available as a PDF in the near future.